Analisis Quality Control Circle (QCC) dan Quality Loss Function (QLF) Dalam Upaya Meminimalkan Tingkat Kerusakan Kemasan - Adhi, Susilo; Mayasari , Andhika; Wira Ghani, Sulung Rahmawan; Muflihah , Nur (Teknik Industri, Fakultas Teknik, Universitas Hasyim Asy'ari, 2025)
Partner companies from various snack food manufacturers during the company’s production process faced problems in the form of high levels of packaging damage, which reached 11,01% exceeding the tolerance limit, this condition has an impact on increasing production cocsts and complaints from consumers. This study aims to identify and reduce the main causes od packaging damage by implementing Quality Control Circle (QCC) and Quality Loss Function (QLF). QCC is used to find the root casuse of the problem with the PDCA stages through tools such as check sheet, pareto diagrams, histograms, fishbone diagrams, stratification, and control charts. While QLF is used to calculate economic losses due to quality that deviates from standarts. The results of the study showed that the most common types of packaging defects were folding packaging, snap packaging, and slip packaging. The main causeative factors include operator negligence, unstable machine settings, materials that do not meet specifications. Recommendations for continuous imptovment include operator training, standardization of SOPs between shifts, machine calibration, and strict supervision of packaging materials.